2001
DOI: 10.1101/gad.935501
|View full text |Cite
|
Sign up to set email alerts
|

Mediator function of the human Rad51B–Rad51C complex in Rad51/RPA-catalyzed DNA strand exchange

Abstract: Five Rad51-like proteins, referred to as Rad51 paralogs, have been described in vertebrates. We show that two of them, Rad51B and Rad51C, are associated in a stable complex. Rad51B-Rad51C complex has ssDNA binding and ssDNA-stimulated ATPase activities. We also examined the functional interaction of Rad51B-Rad51C with Rad51 and RPA. Even though RPA enhances Rad51-catalyzed DNA joint formation via removal of secondary structure in the ssDNA substrate, it can also compete with Rad51 for binding to the substrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
178
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 33 publications
14
178
1
1
Order By: Relevance
“…DISCUSSION Using multiple methods (both in vitro and in vivo) we have shown that RAD51B and RAD51C proteins form a heterocomplex. These studies are consistent with the results of Schild et al (8,18) and Sung (26), indicating an interaction between RAD51B and RAD51C. Unique RAD51B and RAD51C baculoviruses were generated and co-infected into insect cells to pro- duce recombinant proteins, which were co-purified and characterized using RAD51B-and RAD51C-specific antibodies.…”
Section: Rad51c Interacts With Rad51b Within a Larger Complex In Vivosupporting
confidence: 74%
See 1 more Smart Citation
“…DISCUSSION Using multiple methods (both in vitro and in vivo) we have shown that RAD51B and RAD51C proteins form a heterocomplex. These studies are consistent with the results of Schild et al (8,18) and Sung (26), indicating an interaction between RAD51B and RAD51C. Unique RAD51B and RAD51C baculoviruses were generated and co-infected into insect cells to pro- duce recombinant proteins, which were co-purified and characterized using RAD51B-and RAD51C-specific antibodies.…”
Section: Rad51c Interacts With Rad51b Within a Larger Complex In Vivosupporting
confidence: 74%
“…This complex has been shown to perform homologous pairing in the absence of RAD51 (20). In a recent study the RAD51B/RAD51C proteins have been shown to participate in recombinational repair processes similar to the RAD55-RAD57 complex in vitro (26). This would suggest that RAD51C has multiple roles in vivo, pairwise with XRCC3 and RAD51B, or in a larger complex with the other RAD51 paralogs possibly dependent on specific cell type (as has been suggested for the XRCC3/RAD51C complex in brain).…”
Section: Rad51c Interacts With Rad51b Within a Larger Complex In Vivomentioning
confidence: 99%
“…This result has important biological implications demonstrating that RecA/RAD51 BM of HJs can occur in the cell, where SSB/RPA is abundant. This result is also consistent with a mechanism of BM that involves polymerization of RecA/RAD51 on the displaced ssDNA strand; it was shown that under similar conditions RecA and RAD51 can displace SSB/RPA from ssDNA, when SSB/RPA is added to ssDNA prior or at the same time as RecA/RAD51 (29,30).…”
Section: Resultssupporting
confidence: 74%
“…During the course of our research, the Rad51B⅐Rad51C complex was purified in the Sung laboratory (46). They reported that the Rad51B⅐Rad51C complex acts to facilitate the replacement of RPA from the nucleofilaments by Rad51 and to promote the DNA strand exchange activity of Rad51 (46), and they suggest a mediator role for the Rad51B⅐Rad51C complex in HRR. We found, using oligonucleotide DNA substrates, that Rad51C, but not Rad51B, promotes a DNA strand exchange reaction.…”
Section: Discussionmentioning
confidence: 99%